Uncovering patterns of author productivity in educational leadership and management in Indonesia: A bibliometric study using lotka's law - Fadhli, Rahmat; Rahmat, Baiquni; Ibrahim, Cecep; Eka Kurnia, Berlian (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2023)
Background of the study: The rapid development in the field of educational leadership and management (EDLM) recently has led to an increase in the number of publications. In line with this, bibliometric analysis has been widely conducted to assess various fields of study, particularly in Indonesia. The abundance of publications also necessitates an examination of the extent to which authors' productivity levels contribute to the field of EDLM in Indonesia. Purpose: This research aims to explore the pattern of author productivity by testing Lotka's Law on publications in the field of EDLM in Indonesia. Method: The testing is conducted using the complete count and straight count methods to compare the results obtained from both approaches. The data for the study were collected from all 44 Indonesian accredited journals in the EDLM field. A total of 7,796 articles were screened based on specific criteria, resulting in a final sample of 5,158 articles with 6,604 authors (complete count) and 4,301 authors (straight count). Findings: The results of the study indicate that the productivity levels of authors in the field of EDLM in Indonesia do not align with Lotka's law. While, most productive authors tend to publish their publication in a single journal only. Conclusion: The study also reveals a disparity in the productivity levels between the two methods, as well as a tendency for productive authors to publish their work in a single journal.